Factors influencing utilization of birth attendants' services by pregnant women and nursing mothers in Ikole LGA of Ekiti State, Nigeria (2012)
Women and children die everyday from the scourge of maternal and infant/ mortality due to the poor primary health care system in most rural communities and as such, this study intends to explore factors influencing utilisation of traditional birth attendants' services by pregnant women and nursing mothers with children ≤5 years old in Ikole LGA of Ekiti State, Nigeria in a typical rural Yoruba community. A descriptive research design was employed for the study, using both quantitative and qualitative methods of data collection. The sample size was selected through random sampling technique and a total of 250 questionnaires were distributed to the pregnant women and mothers with children ≤5 years old, who were currently attending antenatal and/or postnatal with TBAs and were resident in the Ikole Local Government Area. 25 TBAs were interviewed in five selected communities in-Ikole Local Government-Area of Ekiti State for the study. Findings revealed that majority of the pregnant women and nursing mothers had exclusively utilized. TBAs facility while only. Consequently, the outcome of the study indicates that some women resort to TBAs assistance for spiritual reasons. Generally, the TBAs should be given more training to be aware that they are not “illegal” so that their work does not go underground and becomes dangerous. There should be an integration of TBAs and the health centres as it is practiced in China to deal with the spiritual aspect of health care delivery which makes many people patronize TBAs.